EFISIENSI PENYERAPAN PHOSPAT LIMBAH LAUNDRY MENGGUNAKAN KANGKUNG AIR (Ipomoea aquatic forsk) DAN JERINGAU (Acorus calamus) - Fitri Dewi, M. Faisal, Mariana (Jurnal Teknik Kimia USU, 2015)
Laundry waste contains high phosphate concentrations that exceeding levels in Regulation No. 82 of 2001 about Water Quality Management and Control of Water Pollution.  When the waste is directly discharged into the sewers or river without treatment, it can cause water pollution and lead to eutrophication.  Water spinach (Ipomoea aquatica Forsk) and Jeringau (Acorus Calamus l) might be use to absorb phosphate in laundry waste. The aim of this research is to investigate the efficiency of phosphate absorption by using water spinach and Jeringau. The experiments were carried out in a batch system. The results showed that the reduction efficiency of phosphate by Water spinach and Jeringau was 41.61% and 53.75%, respectively.